PENGARUH LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI BERDAMPAK:PERAN PREFERENSI NON-FINANSIAL DAN PERSEPSI RISIKO - Caritas Ignasia Yeni Thoma; Riki Martusa; Meythi Meythi (Universitas Katolik Indonesia Atma Jaya, 2026)
This study explores how financial literacy influences impact investment decisions within non-profit organizations under the Catholic Church in Indonesia. In addition to examining the direct effect of financial literacy, the research investigates the mediating role of non-financial preferences and assesses the extent to which risk perception affects the decision-making process. Data were collected through a survey of sixty financial decision-makers actively involved in managing organizational funds. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLSSEM) to examine the relationships among variables. The findings of this study indicate that financial literacy not only directly affects investment decisions but also shapes how organizations interpret and integrate social and moral values into their financial strategies. Non-financial preferences serve as a significant bridge between financial orientation and the organization’s social goals. While risk perception has a direct influence on impact investment decisions, it does not moderate the relationship between financial literacy and those decisions. This study highlights the importance of incorporating value-based considerations into financial strategies and contributes to the literature on Socially Responsible Investment (SRI) and Behavioral Finance, especially in the context of organizations based on moral and social values.